Al-Zarnuji’s concept of knowledge (‘ilm) - Huda, Miftachul (SAGE, 2016)
Education is important for every Muslim society as the Prophet made it incumbent on all Muslims. However, the issue of what category of knowledge is permitted for Muslims, the method for imparting this knowledge, and what to impart (content) are arguably the main challenges in Islamic education. Many Muslim scholars have looked at the concept of knowledge from various perspectives. In his monumental work, Ta‘lum al-Muta‘allim, the classical Muslim scholar, Al-Zarnuji, expounds the basic principles of education in Islam, which, indeed, have been used as the teaching methodology by many scholars throughout the Muslim world. Using content analysis, this article evaluates the concept of knowledge and its imperatives in Islam from the perspective of Al-Zarnuji. It was found that Al-Zarnuji classified knowledge into two main categories. One is perceived as the core of society’s survival and is thus seen as binding on the entire society. This is known as fardu kifayah. The other is individually required and is called fardu ‘ayn. He argues that both should be guided by the Islamic religious values. Therefore, Al-Zarnuji considers knowledge as a means for advancement and the perfection of the individual and the society both in this world and the hereafter. This makes his concept of knowledge inseparable from the Islamic ethical values. Al-Zarnuji’s contribution to knowledge lies in the packaging and dissemination of the Islamic academic heritage, particularly, the methodology for teaching and learning which is relevant to all the levels of the education ladder.